2018
DOI: 10.1101/322495
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Loss-of-function in IRF2BPL is associated with neurological phenotypes

Abstract: 53The

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 74 publications
0
7
0
3
Order By: Relevance
“…De novo mutations in the interferon regulatory factor 2 binding proteinlike (IRF2BPL) gene have been recently associated with different neurological phenotypes [1,2]. Clinical features include neurodevelopmental regression or speech and motor developmental delay, seizures, hypotonia, coordination difficulties, dystonia and pyramidal signs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…De novo mutations in the interferon regulatory factor 2 binding proteinlike (IRF2BPL) gene have been recently associated with different neurological phenotypes [1,2]. Clinical features include neurodevelopmental regression or speech and motor developmental delay, seizures, hypotonia, coordination difficulties, dystonia and pyramidal signs.…”
mentioning
confidence: 99%
“…Common clinical features in IRF2BPL mutation carriers include a variety of neurological symptoms from dystonia, ataxia, spasticity, dysarthria/anarthria, dysphagia and epilepsy to neurodevelopmental delay or regression [1][2][3][4]. We also wish to highlight the association of IRF2BPL mutations with keratoconus.…”
mentioning
confidence: 99%
“…Interestingly, all individuals with a combination of neurological symptomatology and keratoconus or other ophthalmological abnormalities and IRF2BPL variants carried de novo truncating variants (Fig. 1), and it has been noted previously that more severe phenotypes were seen in patients with truncating IRF2BPL variants than in those carrying missense variants [6,11]. The remaining reports of patients with this disease do not mention ophthalmological disease except eye movement abnormalities, but severe neurological symptomatology might have overshadowed eye disease.…”
mentioning
confidence: 79%
“…is most often in the first decade of life, although later onset cases have been described. Functional studies have shown that loss-of-function of IRF2BPL, or its homologue in animals, leads to neurodegeneration and is associated with abnormalities in endolysosomal storage [6,10].…”
mentioning
confidence: 99%
“…Finally, a recent report from the UDN and MOSC has linked loss-of-function truncation mutations in the Interferon Regulatory Factor 2 Binding Protein Like ( IRF2BPL ) gene with a syndrome involving severe neurodevelopmental regression, hypotonia, ataxia, seizures, and lack of coordination [ 42 ]. Null mutations in the Drosophila homologue pits (Protein interacting with Ttk69 and Sin3A) are lethal, while partial knockdown of pits by RNA interference produces neurodegenerative phenotypes.…”
Section: Udn and Centers For Mendelian Genomicsmentioning
confidence: 99%